Additive manufacturing social impacts: a conceptual model - Ribeiro, André Gonçalo Mendes (2017)
The additive manufacturing technology, also known as 3D printing, is gaining popularity amongst the general public, the media, and in the industries. It is believed to be a disruptive technology, and so the assessment of social impacts is very important. There are still very few works in this area and social impacts are yet to be identified. The first objective of this dissertation was to identify the possible social impacts caused by the implementation of this technology. There were found eleven social strands that were impacted with the additive manufacturing technology. These strands were: educational; commercial; intellectual property; employment and labour; access to the technology; economic; environment and energy; supply chain; health and occupational hazards; healthcare and safety; and governmental approach. There were found twenty-six social impacts amongst these social components. The second objective was to determine who are the stakeholders by those social impacts. For this we analyze the categories of stakeholders in a product life cycle assessment perspective, and matched the social impacts to the stakeholders’ categories, creating a typology for the additive manufacturing social impacts. Amongst every stakeholder category, a set of sub-categories is proposed for each stakeholder too. The third, and last, objective, fulfilled by this dissertation, was to propose social indicators for the additive manufacturing impacts identified. A list of proposed indicators is found in the dissertation. This dissertation results in a conceptual model to analyze the additive manufacturing social impacts.